Aspects of form and style in Beethoven's string quartets - Biesheuvel, Barbara (Rhodes University, Faculty of Humanities, Department of Music, 1963)
Many books have been written which deal with the subject of form and style in Beethoven's works. Most writers, however, seem to be satisfied with superficial descriptions - in some cases merely programatic - which do not explain the underlying problems and treatment of form. Furthermore, no book exists, to my knowledge, which delves so deeply and with such detail as to deduce with almost certain accuracy the inner coherency of the form. It is the aim of this analysis to approach the problem in this way. The edition used for this purpose is that one published by Ernst Eulenberg Ltd. London WI, which was edited from the autograph M.S. by Professor Dr. Wilhelm Altman. No comparisons are made with other editions, and possible printer's and other errors are not considered. I chose the works to be studied here, the three quartets Op. 59, for two reasons: 1) the string quartet medium is one of the most suitable types of instrumental music for the study of form, 2) the Op. 59 quartets belong to a period in Beethoven's life when he was particularly intent upon experimentation in form and development of dimension.
Keywords: Beethoven, Ludwig van, 1770-1827 -- Quartets, strings